Equal Channel Angular Pressing (ECAP) Process Of Copper Electrodes For Resistance Spot Brazing Application. - Thien Ly, Tran Thi (2007)
This research was performed to investigate the influence of ECA pressing step on the workability of copper electrode used for resistance spot brazing application. The as- received copper material was characterized using optical microscope observation and X- Ray fluorescence analysis.